CHANGES IN THE STARCH AND FIBER FRACTIONS OF FRENCH FRIES: RESPONSE OF FREEZING - Raigond, Pinky; Singh, Brajesh; Kaundal, Bhawana (Potato Journal, 2015)
The changes in the starch and fiber contents of French fries were determined in response to freezing duration. Three Indian potato processing cultivars with high dry matter and low reducing sugars viz. Kufri Frysona, Kufri Chipsona-1 and Kufri Chipsona-3 were used for this study. French fries were prepared, par fried and frozen from these cultivars following the standard protocols. All the determinations were done after full frying of the previously frozen fries. Resistant starch and cellulose contents increased to appreciable amount during freezing of fries. The increase in resistant starch and cellulose content was significant after 30 days of storage. After 180 days, the resistant starch content was 9.49, 9.66 and 8.25 mg/100 mg FW and cellulose content was 11.91, 12.49 and 10.47 mg/100 mg FW in French fries prepared from Kufri Frysona, Kufri Chipsona-1 and Kufri Chipsona-3, respectively. Starch and amylose content first increased up to 48 hours, then decreased up to 15 day and again increased for up to 180 days of freezing. Similar trend was observed for reducing sugar content also. The study suggests that freezing of par-fried French fries up to 180 days may increase the health benefits since the RS content increases up to 9.13% (mean of three cultivars) during this process.